Choroidal vessel changes in acute and chronic central serous chorioretinopathy assessed by en-face Layer-by-Layer comparison and correlation - Younhea Jung; Ho Ra; Sungwon Choi; Seung Hoon Lee; Jiwon Baek (Scientific Reports)
Abstract Purpose To analyze vascular morphologies of layers of the choroid and compare between acute and chronic central serous chorioretinopathy (CSC). Methods A total of 161 (79 acute and 82 chronic) CSC eyes followed up for 6 months were enrolled. Baseline optical coherence tomography (OCT) and OCT angiography (OCTA) data were collected, and choriocapillaris (CC), Sattler’s layer, and Haller’s layer en-face slabs were obtained from OCT and OCTA. Vessel parameter analysis was performed using the OCTA Vascular Analyzer. Results Acute CSC showed higher node numbers, vessel area density, and total vessel length at the CC along with reduced diameter variation, skew, and kurtosis when compared to chronic CSC (all P ≤ 0.032). Acute CSC showed reduced diameter, diameter variation, and skew at Sattler’s layer when compared to chronic CSC (all P ≤ 0.033). Finally, acute CSC showed reduced diameter kurtosis at Haller’s layer when compared to chronic CSC (P = 0.017). There were significant correlations noted among the above-mentioned parameters between each layer, with correlations being more prominent between Sattler’s and Haller’s layers. Conclusion CC change in chronic CSC involved decreased nodes, density, and greater diameter variation, which in turn led to increases in diameter and diameter variations of larger vessels.